PBX1 Attenuates Hair Follicle-Derived Mesenchymal Stem Cell Senescence and Apoptosis by Alleviating Reactive Oxygen Species-Mediated DNA Damage Instead of Enhancing DNA Damage Repair - Wang, Yuan; Sui, Yutong; Lian, Aobo; Han, Xing; Liu, Feilin; Zuo, Kuiyang; Liu, Mingsheng; Sun, Wei; Wang, Ziyu; Liu, Zinan; Zou, Fei; Lu, Rifeng; et al. (Frontiers in Cell and Developmental Biology, 2021)
Tissues and organs undergo structural deterioration and functional decline during aging. DNA damage is considered a major cause of stem cell senescence. Although stem cells develop sophisticated DNA repair systems, when the intrinsic and extrinsic insults exceed the DNA repair capacity, cellular senescence and age-related diseases inevitably occur. Therefore, the prevention and alleviation of DNA damage is an alternative to DNA repair in attenuating stem cell senescence and preventing age-related diseases. Pre-B-cell leukaemia homeobox 1 (PBX1) participates in maintaining the pluripotency of human embryonic and haematopoietic stem cells. Our recent studies showed that PBX1 promotes hair follicle-derived mesenchymal stem cell (HF-MSC) proliferation, decreases cellular senescence and apoptosis, and enhances induced pluripotent stem cell generation. Whether PBX1 attenuates HF-MSC senescence and apoptosis by alleviating DNA damage or by enhancing DNA repair remains unknown. In this study, we aimed to determine the effects of PBX1 on the intrinsic ROS- or extrinsic H2O2-induced cellular senescence of HF-MSCs. To this end, we generated HF-MSCs overexpressing either PBX1, or poly [ADP-ribose] polymerase 1, or both. Our results showed that PBX1 overexpression attenuates HF-MSC senescence and apoptosis by alleviating reactive oxygen species (ROS)-mediated DNA damage instead of enhancing DNA repair. This is the first study to report that PBX1 attenuates stem cell senescence and apoptosis by alleviating DNA damage. It provides new insight into the mechanism of stem cell senescence and lays the foundation for the development of strategies for age-related disease prevention and treatment, and in particular, hair follicle repair and regeneration.